Weapon a visual history of arms and armour (Dorling Kindersley Limited, 2016)
With a spectacular illustrated journey through 4,000 years of weaponry, Weapon: A Visual History of Arms and Armour is the most comprehensive visual reference charting the history of arms and armour worldwide. Follow the evolution of weaponry from stone maces to machine-guns, and discover the brutal history of the warriors who wielded them. Drawing extensively on the treasures of the Royal Armouries Museum, this fully updated guide uniquely details the date, weight, size, and country of origin of these arms. Weapon showcases the function and history of key arms from across the world with fascinating photography, taking you on a journey to discover a wealth of weaponry from crossbows to samurai swords. Delve into the brutal side of history and travel through 4,000 years of mighty weaponry.